Точка невозврата: повесть и рассказы / Полина Дашкова - Дашкова Полина Викторовна (Астрель, 2010)
Экземпляры: ф.3 (2011) / Инвентарный номер: 47275 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 21 / ББК: 84(2Рос=Рус)6